High-wear-resistance steel structural part

By setting up metal plating and coating wear-resistant coating on steel structural parts, the problem of insufficient wear and corrosion resistance in harsh environments is solved, and significant improvements in wear and corrosion resistance are achieved, extending service life and reducing maintenance costs.

CN119875489AActive Publication Date: 2025-04-25CHANGSHU CHANGSHENG HEAVY IND STEEL STRUCTURE CO LTD

Patent Information

Application Number
CN202411958621.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Traditional steel structural parts are prone to surface wear, deformation and failure in harsh environments, and the existing simple surface treatment method cannot effectively improve their wear resistance and corrosion resistance.

Method used

It adopts a structural design including a steel structural member base, metal coating and wear-resistant coating. The metal plating is formed by nickel-chromium alloy and polytetrafluoroethylene particles. The wear-resistant coating consists of silane-modified polyol, fluorine-modified silicon carbide chain extender and rare earth oxide filler. It improves hardness and wear resistance through polyurethane network structure and crosslinking reaction.

Benefits of technology

It significantly improves the wear and corrosion resistance of steel structural parts, extends its service life and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a high-wear-resistance steel structural part which comprises a steel structural part base body, a metal plating layer and a wear-resistant coating, and the wear-resistant coating is obtained by coating a wear-resistant coating. The wear-resistant coating is prepared from the following raw material components in parts by mass: 40 to 60 parts of silane modified polyol, 20 to 30 parts of diphenylmethane diisocyanate, 5 to 15 parts of fluorine modified silicon carbide chain extender, 10 to 20 parts of rare earth oxide filler, 0.1 to 0.2 part of catalyst, 0.4 to 0.8 part of defoaming agent and 20 to 40 parts of solvent. The method has the effect of improving the wear resistance and corrosion resistance of the steel structural part, and the high-wear-resistance steel structural part can keep good working performance for a long time under complex working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of steel structure manufacturing, and in particular to a high wear-resistant steel structure. Background Art

[0002] Steel structures are widely used in many industrial fields. For example, in the mining industry, crushers, screens and other equipment use a large number of steel structures; key components such as tower cranes and cranes in the construction field are also steel structures; and there are also vehicle chassis and bridge support structures in the transportation industry. The working environment in these fields is often harsh, and steel structures face varying degrees of friction, impact and wear, which places strict requirements on their wear resistance.

[0003] Traditional steel structures are usually made of ordinary steel, and the surface treatment process is relatively simple, such as simple anti-rust paint spraying or galvanizing. In terms of wear resistance, the hardness and wear resistance of ordinary steel itself are limited. Under high-load friction and impact, it is easy to suffer from surface wear, deformation, and even failure. Although some simple surface treatment methods can prevent corrosion to a certain extent, the effect of improving wear resistance is not significant, and it cannot meet the needs of long-term stable operation, so it needs to be improved. Summary of the invention

[0004] In order to improve the wear resistance of steel structural parts, the present application provides a high wear-resistant steel structural part.

[0005] The present application provides a high wear-resistant steel structural part adopts the following technical solution:

[0006] A highly wear-resistant steel structural part, comprising a steel structural part substrate, a metal plating layer and a wear-resistant coating, wherein the wear-resistant coating is obtained by coating a wear-resistant coating, and the raw materials for preparing the wear-resistant coating include the following components in parts by mass:

[0007] Silane modified polyol 40-60 parts

[0008] 20-30 parts of diphenylmethane diisocyanate

[0009] Fluorine modified silicon carbide chain extender 5-15 parts

[0010] Rare earth oxide filler 10-20 parts

[0011] Catalyst 0.1-0.2 parts

[0012] Defoamer 0.4-0.8 parts

[0013] 20-40 parts of solvent.

[0014] By setting a metal coating on the steel structure substrate, the corrosion of the substrate by the external environment can be blocked, and a good adhesion basis can be provided for subsequent coatings; the silane-modified polyol and diphenylmethane diisocyanate in the wear-resistant coating interact to form a polyurethane network structure, which has high hardness and good flexibility and can effectively resist wear during friction; the addition of fluorine-modified silicon carbide chain extender further enhances the degree of cross-linking of the coating, improves the wear resistance and hardness of the coating, and the fluorine element it contains can also reduce the surface energy of the coating, reduce the adhesion of dust, water vapor, etc., thereby improving the corrosion resistance; rare earth oxide fillers play a role in enhancing the wear resistance in the coating by virtue of their high hardness and chemical stability, and their redox activity can also inhibit the occurrence of corrosion reactions, further improving the corrosion resistance of steel structures; the synergistic effect of the various components in high-corrosion-resistant steel structures enables them to significantly improve their wear resistance and corrosion resistance in complex use environments, extend their service life, and reduce maintenance costs.

[0015] Preferably, the raw materials for preparing the silane-modified polyol include cage-type silsesquioxane, bisaminosilane coupling agent and polybutylene adipate diol.

[0016] Cage silsesquioxane has a nano-scale cage structure and can be used as a rigid nano-filler to enhance the hardness of the coating and as a supporting skeleton to disperse external forces during friction and reduce wear. The bisaminosilane coupling agent reacts with the active groups on the cage silsesquioxane and successfully introduces the active groups into the cage structure, thereby enhancing the reactivity of the cage silsesquioxane with the polyol, allowing it to chemically bond more tightly and efficiently with polybutylene adipate diol to form a highly cross-linked and stable structure, which can effectively improve the hardness and toughness of the coating, allowing it to better disperse and withstand external forces and reduce wear when dealing with friction. The tightly cross-linked structure effectively blocks the intrusion of external corrosive media, while enhancing the adhesion between the coating and the steel structure substrate, preventing the coating from peeling off and exposing the substrate to the corrosive environment, thereby significantly extending the service life of the steel structure in harsh environments.

[0017] Preferably, the mass ratio of the cage-type silsesquioxane, the bisaminosilane coupling agent and the polybutylene adipate diol is 1:0.13:(15-20).

[0018] The silane-modified polyol prepared according to the above mass ratio has good performance and can effectively improve the wear resistance and corrosion resistance of steel structural parts.

[0019] Preferably, the raw materials for preparing the fluorine-modified nano-silicon carbide chain extender include nano-silicon carbide, perfluorooctyltrichlorosilane and decanediamine.

[0020] Perfluorooctyltrichlorosilane reacts with decanediamine to generate a silane coupling agent containing active amino groups, which then reacts with the hydroxyl groups on the surface of nano-silicon carbide, successfully introducing fluorine into the nano-silicon carbide structure, while allowing long-chain amino groups to exist on the surface of nano-silicon carbide, which can act as a chain extender to introduce nano-silicon carbide into the side chains of polyurethane, strengthen the defects in the molecular chain, and form a more stable and high-strength cross-linked network, so that the high hardness characteristics of nano-silicon carbide can be fully utilized, effectively resisting the scratches and wear of abrasives, and enhancing the wear resistance of the coating; the introduction of fluorine reduces the surface energy of the coating, making it difficult for corrosive media to adhere to and penetrate the coating surface. At the same time, the stable structure formed by the chain extender can effectively block external corrosive substances such as moisture, oxygen, acids and alkalis from invading the steel structure matrix, thereby significantly improving the corrosion resistance of steel structures in harsh environments and extending their service life.

[0021] Preferably, the mass ratio of the nano-silicon carbide, perfluorooctyltrichlorosilane and decanediamine is (4-5):1:0.36.

[0022] Preferably, the fluorine-modified nano-silicon carbide chain extender is prepared by the following steps:

[0023] Perfluorooctyltrichlorosilane and decanediamine are mixed and dispersed in toluene, stirred under the protection of neutral gas, heated to react, and after cooling, the solvent is removed by rotary evaporation to obtain a crude product, and the crude product is recrystallized to obtain a modified fluorine-containing silane; nano-silicon carbide and the modified fluorine-containing silane prepared above are mixed and dispersed in toluene, water is added, heated to stir and react, and after cooling, centrifuged, washed, and dried to obtain a fluorine-modified nano-silicon carbide chain extender.

[0024] The fluorine-modified nano-silicon carbide chain extender prepared according to the above mass ratio and steps can effectively reinforce the polyurethane molecules, thereby improving the wear resistance and corrosion resistance of high-wear-resistant steel structural parts.

[0025] Preferably, the raw materials for preparing the rare earth oxide filler include cerium oxide, lanthanum oxide and a coating polymer.

[0026] Cerium oxide and lanthanum oxide have high hardness and good chemical stability. The coating polymer is wrapped on the surface of rare earth oxide by chemical bonding or physical adsorption to improve its dispersion performance. When steel structural parts are subjected to friction, rare earth oxides as hard points can effectively resist wear. The coating polymer can enhance the compatibility of rare earth oxides with other components in the coating system, making the filler more evenly dispersed in the system, further improving the overall wear resistance. Cerium oxide and lanthanum oxide have certain antioxidant and corrosion resistance and can inhibit the occurrence of corrosion reactions. The coating polymer forms a protective film to prevent external corrosive media from directly contacting rare earth oxides and the steel structural parts matrix, thereby synergistically enhancing the corrosion resistance of steel structural parts, enabling them to maintain good performance in complex and harsh environments and extend their service life.

[0027] Preferably, the raw materials for preparing the coating polymer include polyaspartic acid and polyquaternary ammonium salt.

[0028] Polyaspartic acid contains abundant active functional groups such as carboxyl, etc., which can interact with hydroxyl and other groups on the surface of rare earth oxides by chemical bonding to achieve initial coating, increase the stability and dispersibility of rare earth oxides in the coating system, and thus help improve the wear resistance of steel structures when they are subjected to friction, making rare earth oxides more effectively resistant to wear; polyquaternary ammonium salts have cationic properties, and there are interactions such as electrostatic attraction between them and polyaspartic acid, which further strengthen the coating layer and form a tighter and more stable structure. At the same time, its cationic groups can adsorb anionic corrosive media in the environment and play a corrosion inhibition role. At the same time, this tight coating structure can also prevent external moisture, oxygen and other corrosive substances from penetrating into the surface of rare earth oxides and steel structure substrates, thereby enhancing the corrosion resistance of steel structures and ensuring their long-term stable operation under complex working conditions.

[0029] Preferably, the metal coating comprises nickel-chromium alloy and polytetrafluoroethylene particles.

[0030] Nickel-chromium alloy has good corrosion resistance and hardness, and can provide a preliminary protective barrier for the steel structure matrix, effectively resisting the erosion of moisture, oxygen and some corrosive chemicals in the external environment, and slowing down the corrosion rate of the matrix. At the same time, the hardness of nickel-chromium alloy also helps to improve the wear resistance of steel structures and help resist damage caused by friction; polytetrafluoroethylene particles further optimize the performance of the coating. Polytetrafluoroethylene has an extremely low friction coefficient. When steel structures are subjected to friction, these particles can lubricate the surface, reduce friction resistance, reduce the degree of wear, and enhance the wear resistance of the coating; in addition, polytetrafluoroethylene particles also have good chemical stability and non-stickiness, which can prevent corrosive media from adhering to and accumulating on the surface of the coating, and synergize with nickel-chromium alloy to further improve the corrosion resistance of the coating.

[0031] Preferably, the high wear-resistant steel structural part is prepared by the following steps:

[0032] The steel structure substrate is degreased and soaked in a dilute hydrochloric acid solution to obtain an activated steel structure; an electroplating solution is prepared, the electroplating solution includes nickel sulfate, chromic anhydride, sodium sulfate, boric acid and polytetrafluoroethylene particles, and the electroplating solution is obtained by ultrasonic treatment; the activated steel structure is used as a cathode and a nickel-chromium alloy is used as an anode, and the plating solution is stirred during electroplating to obtain a steel structure with a metal coating; a wear-resistant coating is coated on the surface of the steel structure with the metal coating, and after heating and curing, a high-wear-resistant steel structure is obtained.

[0033] The highly wear-resistant steel structural parts prepared according to the above steps have good corrosion resistance and wear resistance, and can maintain good working performance for a long time under complex working conditions.

[0034] In summary, the present application includes at least one of the following beneficial technical effects:

[0035] By setting a metal coating on the steel structure substrate, the corrosion of the substrate by the external environment can be blocked, and a good adhesion basis can be provided for subsequent coatings; the silane-modified polyol and diphenylmethane diisocyanate in the wear-resistant coating interact to form a polyurethane network structure, which has high hardness and good flexibility and can effectively resist wear during friction; the addition of fluorine-modified silicon carbide chain extender further enhances the degree of cross-linking of the coating, improves the wear resistance and hardness of the coating, and the fluorine element it contains can also reduce the surface energy of the coating, reduce the adhesion of dust, water vapor, etc., thereby improving the corrosion resistance; rare earth oxide fillers play a role in enhancing the wear resistance in the coating by virtue of their high hardness and chemical stability, and their redox activity can also inhibit the occurrence of corrosion reactions, further improving the corrosion resistance of steel structures; the synergistic effect of the various components in high-corrosion-resistant steel structures enables them to significantly improve their wear resistance and corrosion resistance in complex use environments, extend their service life, and reduce maintenance costs.

[0036] Cage silsesquioxane has a nano-scale cage structure and can be used as a rigid nano-filler to enhance the hardness of the coating and as a supporting skeleton to disperse external forces during friction and reduce wear. The bisaminosilane coupling agent reacts with the active groups on the cage silsesquioxane and successfully introduces the active groups into the cage structure, thereby enhancing the reactivity of the cage silsesquioxane with the polyol, allowing it to chemically bond more tightly and efficiently with polybutylene adipate diol to form a highly cross-linked and stable structure, which can effectively improve the hardness and toughness of the coating, allowing it to better disperse and withstand external forces and reduce wear when dealing with friction. The tightly cross-linked structure effectively blocks the intrusion of external corrosive media, while enhancing the adhesion between the coating and the steel structure substrate, preventing the coating from peeling off and exposing the substrate to the corrosive environment, thereby significantly extending the service life of the steel structure in harsh environments.

[0037] Perfluorooctyltrichlorosilane reacts with decanediamine to generate a silane coupling agent containing active amino groups, which then reacts with the hydroxyl groups on the surface of nano-silicon carbide, successfully introducing fluorine into the nano-silicon carbide structure, while allowing long-chain amino groups to exist on the surface of nano-silicon carbide, which can act as a chain extender to introduce nano-silicon carbide into the side chains of polyurethane, strengthen the defects in the molecular chain, and form a more stable and high-strength cross-linked network, so that the high hardness characteristics of nano-silicon carbide can be fully utilized, effectively resisting the scratches and wear of abrasives, and enhancing the wear resistance of the coating; the introduction of fluorine reduces the surface energy of the coating, making it difficult for corrosive media to adhere to and penetrate the coating surface. At the same time, the stable structure formed by the chain extender can effectively block external corrosive substances such as moisture, oxygen, and acids and alkalis from invading the steel structure matrix, thereby significantly improving the corrosion resistance of steel structures in harsh environments and extending their service life. DETAILED DESCRIPTION

[0038] The present application discloses a highly wear-resistant steel structural part. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments:

[0039] Raw material description: cage silsesquioxane (CAS: 160185-24-0), bisaminosilane coupling agent KH-792 (CAS No.: 1760-24-3), dibutyltin dilaurate (CAS No.: 77-58-7), polybutylene adipate diol (CAS No.: 150923-12-9), molecular weight 2000, dibutyltin oxide (CAS No.: 818-08-6), perfluorooctyltrichlorosilane (CAS No.: 78560-45-9), decanediamine (CAS No.: 646-25-3), nanocarbon The silica particle size is 50 nm, polyaspartic acid (CAS No.: 25608-40-6), the molecular weight is 1000, the polyquaternary ammonium salt is polydimethyldiallylammonium chloride (CAS No.: 26062-79-3), diphenylmethane diisocyanate (CAS No.: 26447-40-5), the solvent is N, N-dimethylformamide, the catalyst is dibutyltin dilaurate, the defoamer model is AKN-3386, purchased from Foshan Qianyou Chemical Co., Ltd., the polytetrafluoroethylene particle size is 0.1 μm, octyltrichlorosilane (CAS: 5283-66-9).

[0040] Example 1

[0041] Preparation of silane-modified polyols

[0042] 6.2 g of cage-type silsesquioxane and 0.8 g of bisaminosilane coupling agent were dispersed in 20 mL of N, N-dimethylformamide, and stirred at 200 rpm for 15 min under nitrogen protection to obtain a silane-modified liquid; 0.1 g of dibutyltin dilaurate was added to the silane-modified liquid, the temperature was raised to 80° C., and the reaction was stirred at 200 rpm for 4 h to obtain a preliminary modified product; 93 g of polybutylene adipate diol and 0.5 g of dibutyltin oxide were added to the preliminary modified product, the temperature was raised to 300 rpm for 15 min under nitrogen protection, the temperature was raised to 140° C. and the reaction was performed for 8 h, and the solvent was removed by reduced pressure distillation after cooling to below 30° C., washed with ethanol, and vacuum dried at 60° C. to obtain a modified polyol.

[0043] Preparation of fluorine-modified nano-silicon carbide chain extender

[0044] 3.73g of perfluorooctyltrichlorosilane and 1.34g of decanediamine were mixed and dispersed in 20mL of toluene, stirred at 300rpm for 15min under nitrogen protection, heated to 60°C and reacted for 6h, and after cooling to below 30°C, the solvent was removed by rotary evaporation to obtain a crude product, and the crude product was recrystallized to obtain a modified fluorine-containing silane; 14.93g of nano-silicon carbide and the modified fluorine-containing silane prepared above were mixed and dispersed in 50mL of toluene, 2mL of deionized water was added, the temperature was raised to 80°C and stirred at 500rpm for 6h, after cooling to below 30°C, centrifuged, washed with anhydrous ethanol, and vacuum dried at 60°C to obtain a fluorine-modified nano-silicon carbide chain extender.

[0045] Preparation of rare earth oxide fillers

[0046] The cerium oxide and lanthanum oxide are ground separately and passed through a 200-mesh sieve to obtain pretreated cerium oxide and lanthanum oxide; the pretreated cerium oxide and lanthanum oxide are mixed in a mass ratio of 1:1 to obtain a rare earth mixture, 50g of the rare earth mixture and 10g of polyaspartic acid are dispersed in 100mL of deionized water, the temperature is raised to 60°C and stirred at a speed of 500rpm for reaction for 4h to obtain a preliminary modified suspension; 15g of polydimethyldiallylammonium chloride is dispersed in 30mL of deionized water to obtain a polyquaternary ammonium salt solution, the preliminary modified suspension is added dropwise to the polyquaternary ammonium salt solution within 1h, the temperature is raised to 80°C after the addition is completed, the reaction is carried out for 4h, and after cooling to 300°C, a precipitate is obtained by centrifugation, the precipitate is washed with deionized water, and dried at 60°C to obtain a rare earth oxide filler.

[0047] Preparation of wear-resistant coatings

[0048] 40g of silane-modified polyol, 20g of diphenylmethane diisocyanate and 5g of fluorine-modified silicon carbide chain extender were mixed and dispersed in 20g of solvent, 0.1g of catalyst was added, the temperature was raised to 80°C and stirred at 500rpm for 3h to obtain a prepolymer; 10g of rare earth oxide filler was added to the prepolymer, stirred at 1000rpm for 30min, 0.4g of defoamer was added, stirred at 500rpm for 15min to obtain a coating, and the coating was passed through a 100-mesh filter to obtain a wear-resistant coating.

[0049] Preparation of high wear-resistant steel structural parts

[0050] The steel structure substrate is degreased and immersed in a diluted hydrochloric acid solution with a mass concentration of 5% for 3 minutes to obtain an activated steel structure; an electroplating solution is prepared, the electroplating solution is an aqueous solution, and the electroplating solution includes 300g / L nickel sulfate, 200g / L chromic anhydride, 50g / L sodium sulfate, 30g / L boric acid, 10g / L polytetrafluoroethylene particles, and ultrasonic treatment for 30 minutes to obtain an electroplating solution; the activated steel structure is used as a cathode, and the nickel-chromium alloy is used as an anode, the plating solution is stirred at a speed of 200rpm, the current density is 4A / dm2, the electroplating temperature is 60°C, and the electroplating time is 30min to obtain a steel structure with a metal coating; a wear-resistant coating is coated on the surface of the steel structure with a metal coating, and it is heated and cured at 100°C for 2h to obtain a high wear-resistant steel structure.

[0051] Example 2

[0052] Preparation of silane-modified polyols

[0053] 4.73 g of cage-type silsesquioxane and 0.62 g of bisaminosilane coupling agent were dispersed in 20 mL of N, N-dimethylformamide, and stirred at 200 rpm for 15 min under nitrogen protection to obtain a silane-modified liquid; 0.1 g of dibutyltin dilaurate was added to the silane-modified liquid, the temperature was raised to 80° C., and the reaction was stirred at 200 rpm for 4 h to obtain a preliminary modified product; 94.65 g of polybutylene adipate diol and 0.5 g of dibutyltin oxide were added to the preliminary modified product, the temperature was raised to 300 rpm for 15 min under nitrogen protection, the temperature was raised to 140° C. and the reaction was performed for 8 h, and the solvent was removed by reduced pressure distillation after cooling to below 30° C., washed with ethanol, and vacuum dried at 60° C. to obtain a modified polyol.

[0054] Preparation of fluorine-modified nano-silicon carbide chain extender

[0055] 3.15g of perfluorooctyltrichlorosilane and 1.13g of decanediamine were mixed and dispersed in 20mL of toluene, stirred at 300rpm for 15min under nitrogen protection, heated to 60°C and reacted for 6h, and after cooling to below 30°C, the solvent was removed by rotary evaporation to obtain a crude product, and the crude product was recrystallized to obtain a modified fluorine-containing silane; 15.72g of nano-silicon carbide and the modified fluorine-containing silane prepared above were mixed and dispersed in 50mL of toluene, 2mL of deionized water was added, the temperature was raised to 80°C and stirred at 500rpm for 6h, after cooling to below 30°C, centrifuged, washed with anhydrous ethanol, and vacuum dried at 60°C to obtain a fluorine-modified nano-silicon carbide chain extender.

[0056] Preparation of rare earth oxide fillers

[0057] The cerium oxide and lanthanum oxide are ground separately and passed through a 200-mesh sieve to obtain pretreated cerium oxide and lanthanum oxide; the pretreated cerium oxide and lanthanum oxide are mixed in a mass ratio of 1:1 to obtain a rare earth mixture, 50g of the rare earth mixture and 10g of polyaspartic acid are dispersed in 100mL of deionized water, the temperature is raised to 60°C and stirred at a speed of 500rpm for reaction for 4h to obtain a preliminary modified suspension; 15g of polydimethyldiallylammonium chloride is dispersed in 30mL of deionized water to obtain a polyquaternary ammonium salt solution, the preliminary modified suspension is added dropwise to the polyquaternary ammonium salt solution within 1h, the temperature is raised to 80°C after the addition is completed, the reaction is carried out for 4h, and after cooling to 300°C, a precipitate is obtained by centrifugation, the precipitate is washed with deionized water, and dried at 60°C to obtain a rare earth oxide filler.

[0058] Preparation of wear-resistant coatings

[0059] 60g of silane-modified polyol, 30g of diphenylmethane diisocyanate and 15g of fluorine-modified silicon carbide chain extender were mixed and dispersed in 40g of solvent, 0.2g of catalyst was added, the temperature was raised to 80°C and stirred at 500rpm for 3h to obtain a prepolymer; 20g of rare earth oxide filler was added to the prepolymer, stirred at 1000rpm for 30min, 0.8g of defoamer was added, stirred at 500rpm for 15min to obtain a coating, and the coating was filtered through a 100-mesh filter to obtain a wear-resistant coating.

[0060] Preparation of high wear-resistant steel structural parts

[0061] The steel structure substrate is degreased and immersed in a diluted hydrochloric acid solution with a mass concentration of 5% for 3 minutes to obtain an activated steel structure; an electroplating solution is prepared, the electroplating solution is an aqueous solution, and the electroplating solution includes 300g / L nickel sulfate, 200g / L chromic anhydride, 50g / L sodium sulfate, 30g / L boric acid, 10g / L polytetrafluoroethylene particles, and ultrasonic treatment for 30 minutes to obtain an electroplating solution; the activated steel structure is used as a cathode, and the nickel-chromium alloy is used as an anode, the plating solution is stirred at a speed of 200rpm, the current density is 4A / dm2, the electroplating temperature is 60°C, and the electroplating time is 30min to obtain a steel structure with a metal coating; a wear-resistant coating is coated on the surface of the steel structure with a metal coating, and it is heated and cured at 100°C for 2h to obtain a high wear-resistant steel structure.

[0062] Example 3

[0063] Preparation of silane-modified polyols

[0064] 5.37 g of cage-type silsesquioxane and 0.7 g of bisaminosilane coupling agent were dispersed in 20 mL of N, N-dimethylformamide, and stirred at 200 rpm for 15 min under nitrogen protection to obtain a silane-modified liquid; 0.1 g of dibutyltin dilaurate was added to the silane-modified liquid, the temperature was raised to 80° C., and the reaction was stirred at 200 rpm for 4 h to obtain a preliminary modified product; 93.93 g of polybutylene adipate diol and 0.5 g of dibutyltin oxide were added to the preliminary modified product, the temperature was raised to 300 rpm for 15 min under nitrogen protection, the temperature was raised to 140° C. and the reaction was performed for 8 h, and the solvent was removed by reduced pressure distillation after cooling to below 30° C., washed with ethanol, and vacuum dried at 60° C. to obtain a modified polyol.

[0065] Preparation of fluorine-modified nano-silicon carbide chain extender

[0066] 3.41g of perfluorooctyltrichlorosilane and 1.23g of decanediamine were mixed and dispersed in 20mL of toluene, stirred at 300rpm for 15min under nitrogen protection, heated to 60°C and reacted for 6h, and after cooling to below 30°C, the solvent was removed by rotary evaporation to obtain a crude product, and the crude product was recrystallized to obtain a modified fluorine-containing silane; 15.36g of nano-silicon carbide and the modified fluorine-containing silane prepared above were mixed and dispersed in 50mL of toluene, 2mL of deionized water was added, the temperature was raised to 80°C and stirred at 500rpm for 6h, after cooling to below 30°C, centrifuged, washed with anhydrous ethanol, and vacuum dried at 60°C to obtain a fluorine-modified nano-silicon carbide chain extender.

[0067] Preparation of rare earth oxide fillers

[0068] The cerium oxide and lanthanum oxide are ground separately and passed through a 200-mesh sieve to obtain pretreated cerium oxide and lanthanum oxide; the pretreated cerium oxide and lanthanum oxide are mixed in a mass ratio of 1:1 to obtain a rare earth mixture, 50g of the rare earth mixture and 10g of polyaspartic acid are dispersed in 100mL of deionized water, the temperature is raised to 60°C and stirred at a speed of 500rpm for reaction for 4h to obtain a preliminary modified suspension; 15g of polydimethyldiallylammonium chloride is dispersed in 30mL of deionized water to obtain a polyquaternary ammonium salt solution, the preliminary modified suspension is added dropwise to the polyquaternary ammonium salt solution within 1h, the temperature is raised to 80°C after the addition is completed, the reaction is carried out for 4h, and after cooling to 300°C, a precipitate is obtained by centrifugation, the precipitate is washed with deionized water, and dried at 60°C to obtain a rare earth oxide filler.

[0069] Preparation of wear-resistant coatings

[0070] 50g of silane-modified polyol, 25g of diphenylmethane diisocyanate and 10g of fluorine-modified silicon carbide chain extender were mixed and dispersed in 30g of solvent, 0.15g of catalyst was added, the temperature was raised to 80°C and stirred at 500rpm for 3h to obtain a prepolymer; 15g of rare earth oxide filler was added to the prepolymer, stirred at 1000rpm for 30min, 0.6g of defoamer was added, stirred at 500rpm for 15min to obtain a coating, and the coating was filtered through a 100-mesh filter to obtain a wear-resistant coating.

[0071] Preparation of high wear-resistant steel structural parts

[0072] The steel structure substrate is degreased and immersed in a diluted hydrochloric acid solution with a mass concentration of 5% for 3 minutes to obtain an activated steel structure; an electroplating solution is prepared, the electroplating solution is an aqueous solution, and the electroplating solution includes 300g / L nickel sulfate, 200g / L chromic anhydride, 50g / L sodium sulfate, 30g / L boric acid, 10g / L polytetrafluoroethylene particles, and ultrasonic treatment for 30 minutes to obtain an electroplating solution; the activated steel structure is used as a cathode, and the nickel-chromium alloy is used as an anode, the plating solution is stirred at a speed of 200rpm, the current density is 4A / dm2, the electroplating temperature is 60°C, and the electroplating time is 30min to obtain a steel structure with a metal coating; a wear-resistant coating is coated on the surface of the steel structure with a metal coating, and it is heated and cured at 100°C for 2h to obtain a high wear-resistant steel structure.

[0073] Example 4

[0074] Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of cage-type silsesquioxane used is 8.98 g, the amount of bisaminosilane coupling agent used is 1.17 g, and the amount of polybutylene adipate diol used is 89.85 g.

[0075] Example 5

[0076] Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of cage-type silsesquioxane used is 3.21 g, the amount of bisaminosilane coupling agent used is 0.42 g, and the amount of polybutylene adipate diol used is 96.37 g.

[0077] Example 6

[0078] Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, no bisaminosilane coupling agent is added when preparing the silane-modified polyol.

[0079] Example 7

[0080] Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of nano-silicon carbide used is 13.76 g, the amount of perfluorooctyltrichlorosilane used is 4.59 g, and the amount of decanediamine used is 1.65 g.

[0081] Example 8

[0082] Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of nano-silicon carbide used is 16.3 g, the amount of perfluorooctyltrichlorosilane used is 2.72 g, and the amount of decanediamine used is 0.98 g.

[0083] Example 9

[0084] Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, no decanediamine is added when preparing the fluorine-modified nano-silicon carbide chain extender.

[0085] Example 10

[0086] Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, perfluorooctyltrichlorosilane is replaced by octyltrichlorosilane.

[0087] Embodiment 11

[0088] Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that polyaspartic acid is not added when preparing the rare earth oxide filler in Example 11.

[0089] Example 12

[0090] Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, no polyquaternary ammonium salt is added when preparing the rare earth oxide filler.

[0091] Example 13

[0092] Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that no polytetrafluoroethylene particles are added when preparing the metal coating in Example 13.

[0093] Comparative Example 1

[0094] Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the silane-modified polyol is replaced by polybutylene adipate diol.

[0095] Comparative Example 2

[0096] Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the fluorine-modified silicon carbide chain extender is replaced by decanediamine.

[0097] Performance testing

[0098] (1) GB / T 26651-2011 Wear-resistant steel castings was selected as the standard. The wear resistance of the samples was tested using the MMV-1A multifunctional material friction behavior tester. The grinding material GCr15 with a diameter of 5 mm was used. The grinding speed was 250 rpm for 30 min under a load of 400 g. The wear amount of the samples was calculated. Three samples were prepared for each sample. The average value was taken after measurement. The results are recorded in Table 1.

[0099] (2) Corrosion resistance test: In a sodium chloride aqueous solution with a mass content of 10%, the scanning rate was 1 mv / s, and the corrosion current density of the sample with a scanning detection area of ​​1 cm3 was measured. Each sample was tested three times and the average value was taken after measurement. The results are recorded in Table 1.

[0100] Table 1 Test results of wear resistance and corrosion resistance of steel structural parts Test results <![CDATA[Wear amount (10 -3 g / (N·m))]]> <![CDATA[Corrosion current density (μA / cm 2 )]]> Example 1 0.76 0.028 Example 2 0.75 0.026 Example 3 0.73 0.025 Example 4 0.85 0.038 Example 5 0.82 0.033 Example 6 0.91 0.042 Example 7 0.83 0.036 Example 8 0.85 0.039 Example 9 0.98 0.043 Example 10 0.81 0.054 Embodiment 11 0.85 0.045 Example 12 0.87 0.044 Example 13 0.93 0.051 Comparative Example 1 1.06 0.056 Comparative Example 2 1.23 0.068

[0101] It can be seen from Table 1 that the wear loss of Examples 1-3 is less than 0.76*10-3g / (N·m), and the corrosion current density is less than 0.028μA / cm2, which shows that the high-wear-resistant steel structural parts prepared in this application have good wear resistance and corrosion resistance.

[0102] As can be seen from Table 1, the only difference between Examples 4, 5, and 6 and Example 3 is that in Example 4, the mass ratio of cage silsesquioxane, bisaminosilane coupling agent, and polybutylene adipate diol is 1:0.13:10, in Example 5, the mass ratio of cage silsesquioxane, bisaminosilane coupling agent, and polybutylene adipate diol is 1:0.13:30, and in Example 6, no bisaminosilane coupling agent is added when preparing the silane-modified polyol. Compared with Example 3, the wear resistance and corrosion resistance of Examples 4, 5, and 6 are reduced; this is because too much cage silsesquioxane may agglomerate and become a stress concentration point, forming shedding cracks during friction, thereby affecting the wear resistance and corrosion resistance; too little cage silsesquioxane modification effect is insufficient, and the performance is reduced; without adding bisaminosilane coupling agent, the reaction activity decreases, and the crosslinking degree of the system decreases, thereby affecting the wear resistance and corrosion resistance.

[0103] As shown in Table 1, the difference between Examples 7-10 and Example 3 is that the mass ratio of nano silicon carbide, perfluorooctyltrichlorosilane and decanediamine in Example 7 is 3:1:0.36, the mass ratio of nano silicon carbide, perfluorooctyltrichlorosilane and decanediamine in Example 8 is 6:1:0.36, decanediamine is not added when preparing the fluorine-modified nano silicon carbide chain extender in Example 9, and perfluorooctyltrichlorosilane is replaced by octyltrichlorosilane in Example 10. Compared with Example 3, Examples 7-10 have better wear resistance and corrosion resistance. The corrosion resistance is reduced; this is because the mass ratio between nano-silicon carbide and fluorinated silane is changed. Too much or too little fluorinated silane will affect the modification effect of the chain extender, and the stability of the polyurethane molecular chain will decrease, thereby affecting the wear resistance and corrosion resistance. If decanediamine is not added, fluorinated silane can only modify the surface of nano-silicon carbide and cannot be introduced as a side chain, thereby reducing the degree of crosslinking. Replacing fluorinated silane with ordinary silane lacks the introduction of fluorine atoms, the surface energy of the coating increases, and the corrosion resistance deteriorates.

[0104] As can be seen from Table 1, the only difference between Examples 11 and 12 and Example 3 is that: in Example 11, no polyaspartic acid is added when preparing the rare earth oxide filler, and in Example 12, no polyquaternary ammonium salt is added when preparing the rare earth oxide filler. Compared with Example 3, the wear resistance and corrosion resistance of Examples 11 and 12 are reduced; this is because the failure to add polyaspartic acid or polyquaternary ammonium salt will affect the stability and synergistic effect of the coating layer, thereby affecting the wear resistance of the rare earth oxide, and the corrosive medium is more easily infiltrated, thereby reducing the wear resistance and corrosion resistance.

[0105] It can be seen from Table 1 that the only difference between Example 13 and Example 3 is that: in Example 13, no polytetrafluoroethylene particles are added when preparing the metal coating, and compared with Example 3, Example 13 has reduced wear resistance and corrosion resistance; this is because no polytetrafluoroethylene particles are added when preparing the metal coating, and the lack of introduction of polytetrafluoroethylene particles reduces surface lubricity and increases friction resistance, and the surface of the coating is smoother, and the bonding strength with the coating is reduced, and corrosive media are easier to invade, thereby reducing wear resistance and corrosion resistance.

[0106] It can be seen from Table 1 that the only difference between Comparative Example 1 and Example 3 is that: Comparative Example 1 replaces the silane-modified polyol with polybutylene adipate diol, and compared with Example 3, the wear resistance and corrosion resistance of Comparative Example 1 are reduced; this is because the silane-modified polyol is replaced with polybutylene adipate diol, which lacks the nanocage structure of cage-type silsesquioxane, the wear resistance is reduced, the crosslinking density of the system is reduced, and thus the corrosion resistance is reduced.

[0107] As can be seen from Table 1, the only difference between Comparative Example 2 and Example 3 is that: Comparative Example 2 replaces the fluorine-modified silicon carbide chain extender with decanediamine. Compared with Example 3, the wear resistance and corrosion resistance of Comparative Example 2 are reduced; this is because the lack of the reinforcing effect of silicon carbide increases the defects between the polyurethane molecules, and the hardness decreases, and the wear resistance deteriorates. At the same time, the lack of fluorosilane increases the surface energy, the corrosive medium is easier to invade, and the corrosion resistance is reduced.

[0108] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A highly wear-resistant steel structural part, characterized in that: It includes a steel structure substrate, a metal plating layer and a wear-resistant coating, wherein the wear-resistant coating is obtained by coating a wear-resistant coating, and the raw materials for preparing the wear-resistant coating include the following components in parts by mass: Silane modified polyol 40-60 parts 20-30 parts of diphenylmethane diisocyanate Fluorine modified silicon carbide chain extender 5-15 parts Rare earth oxide filler 10-20 parts Catalyst 0.1-0.2 parts Defoamer 0.4-0.8 parts 20-40 parts of solvent.

2. A highly wear-resistant steel structural member according to claim 1, characterized in that: The raw materials for preparing the silane-modified polyol include cage-type silsesquioxane, a bisaminosilane coupling agent and polybutylene adipate diol.

3. A highly wear-resistant steel structural member according to claim 2, characterized in that: The mass ratio of the cage-type silsesquioxane, the bisaminosilane coupling agent and the polybutylene adipate diol is 1:0.13:(15-20).

4. A highly wear-resistant steel structural member according to claim 1, characterized in that: The raw materials for preparing the fluorine-modified nano-silicon carbide chain extender include nano-silicon carbide, perfluorooctyltrichlorosilane and decanediamine.

5. A highly wear-resistant steel structural member according to claim 4, characterized in that: The mass ratio of the nano silicon carbide, perfluorooctyltrichlorosilane and decanediamine is (4-5):1:0.

36.

6. A highly wear-resistant steel structural component according to claim 5, characterized in that: The fluorine-modified nano-silicon carbide chain extender is prepared by the following steps: Perfluorooctyltrichlorosilane and decanediamine are mixed and dispersed in toluene, stirred under the protection of neutral gas, heated to react, and after cooling, the solvent is removed by rotary evaporation to obtain a crude product, and the crude product is recrystallized to obtain a modified fluorine-containing silane; nano-silicon carbide and the modified fluorine-containing silane prepared above are mixed and dispersed in toluene, water is added, heated to stir and react, and after cooling, centrifuged, washed, and dried to obtain a fluorine-modified nano-silicon carbide chain extender.

7. The high wear-resistant steel structural component according to claim 1, characterized in that: The raw materials for preparing the rare earth oxide filler include cerium oxide, lanthanum oxide and coating polymer.

8. A highly wear-resistant steel structural member according to claim 7, characterized in that: The raw materials for preparing the coating polymer include polyaspartic acid and polyquaternary ammonium salt.

9. The high wear-resistant steel structural component according to claim 1, characterized in that: The metal coating includes nickel-chromium alloy and polytetrafluoroethylene particles.

10. A highly wear-resistant steel structural member according to any one of claims 1 to 9, characterized in that: The highly wear-resistant steel structural part is prepared by the following steps: The steel structure substrate is degreased and soaked in a dilute hydrochloric acid solution to obtain an activated steel structure; an electroplating solution is prepared, the electroplating solution includes nickel sulfate, chromic anhydride, sodium sulfate, boric acid and polytetrafluoroethylene particles, and the electroplating solution is obtained by ultrasonic treatment; the activated steel structure is used as a cathode and a nickel-chromium alloy is used as an anode, and the plating solution is stirred during electroplating to obtain a steel structure with a metal coating; a wear-resistant coating is coated on the surface of the steel structure with the metal coating, and after heating and curing, a high-wear-resistant steel structure is obtained.

Citation Information

Patent Citations

  • Preparation method of high-strength heat-resistant modified polyurethane elastomer

    CN109111727A

  • Wear-resistant non-stick pan coating and preparation method thereof

    CN118291035A

  • Impact-resistant polyurethane material and preparation method thereof

    CN118895044A

  • Polyurethane dispersions containing POSS nanoparticles

    US20080108773A1

Cited By

  • Preparation process of wear-resistant coating on surface of forged wear-resistant part

    CN122234645A